2017
DOI: 10.1016/j.jhep.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA in hepatocellular carcinoma: Mechanisms, biomarkers and therapeutic targets

Abstract: The majority of the human genome is not translated into proteins but can be transcribed into RNA. Even though the resulting non-coding RNAs (ncRNAs) do not encode for proteins, they contribute to diseases such as cancer. Here, we review examples of the functions of ncRNAs in liver cancer and their potential use for the detection and treatment of liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
269
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(280 citation statements)
references
References 210 publications
6
269
0
Order By: Relevance
“…The results showed that AUC for plasma DANCR was 0.868 which was higher than that for AFP (AUC = 0.744) when differentiating patients with HCC from non-HCC patients [112] . Besides these circulating lncRNAs, JPX, UCA1 and WRAP53 were found increased in HCC patients [106,113,114] alone or in combination with other lncRNAs, miRNAs or serum biomarkers [115] . Many reports have indicated that the deregulation of lncRNAs plays important roles in occurrence and progression of HCC however further studies are needed in order to use these as biomarkers.…”
Section: Circulating Non-coding Rnamentioning
confidence: 97%
“…The results showed that AUC for plasma DANCR was 0.868 which was higher than that for AFP (AUC = 0.744) when differentiating patients with HCC from non-HCC patients [112] . Besides these circulating lncRNAs, JPX, UCA1 and WRAP53 were found increased in HCC patients [106,113,114] alone or in combination with other lncRNAs, miRNAs or serum biomarkers [115] . Many reports have indicated that the deregulation of lncRNAs plays important roles in occurrence and progression of HCC however further studies are needed in order to use these as biomarkers.…”
Section: Circulating Non-coding Rnamentioning
confidence: 97%
“…Aberrant expression of lncRNAs has been observed in many types of cancers [11-13]. Previous profile studies of lncRNA expression have documented the dysregulation of a series of lncRNAs in HCC including LncRNA DQ786243 (LncDQ) [14].…”
Section: Introductionmentioning
confidence: 99%
“…20 This study showed that RP11 is associated with elevated EMT as well as poor prognosis in 75 patients with liver cancer. 20 This study showed that RP11 is associated with elevated EMT as well as poor prognosis in 75 patients with liver cancer.…”
Section: Discussionmentioning
confidence: 74%